2012
DOI: 10.1089/gtmb.2011.0225
|View full text |Cite
|
Sign up to set email alerts
|

Role of MDR1 C3435T and GABRG2 C588T Gene Polymorphisms in Seizure Occurrence and MDR1 Effect on Anti-Epileptic Drug (Phenytoin) Absorption

Abstract: Our results show that the MDR1 3435T and GABRG2 588T alleles play a role in seizure occurrence. Moreover, the MDR1 3435T allele also affects PHT absorption. We suggest MDR1 C3435T and GABRG2 C588T genotyping would be of value in order to lower the risk of concentration-dependent drug toxicity and for better patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
2
28
3
Order By: Relevance
“…A lower response rate in carriers of the 2677TT genotype was reported [192], whereas 3435TT had no significant effect [193]. For phenytoin, 3435CC seems to confer a lower C 0 [194] and an increased resistance rate [195]. For valproic acid, the available studies did not find a significant effect on kinetics [196] or the response rate [197].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…A lower response rate in carriers of the 2677TT genotype was reported [192], whereas 3435TT had no significant effect [193]. For phenytoin, 3435CC seems to confer a lower C 0 [194] and an increased resistance rate [195]. For valproic acid, the available studies did not find a significant effect on kinetics [196] or the response rate [197].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…However subsequent studies had provided conflicting results and failed to prove the original findings [14,15,16,17]. Moreover, other studies on different ethnic populations reported the opposite with 3435T homozygosity was the accused of resistance [18,19,20]. Sayyah and colleagues found in their study on idiopathic Iranian epileptic patients that there were more patients with CT and TT genotypes among those with lower number of seizures, and more patients with CC genotype among those with higher number of seizures [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis suggested a correlation between rs1045642 and tacrolimus pharmacokinetics (Li et al, 2012). Other studies connect this SNP with therapeutic outcomes in gastric, lung, blood, and other cancers Yan et al, 2011) and responses to anti-epileptic (Ponnala et al, 2012) and rheumatoid arthritis drugs (Chen et al, 2011). Moreover, rs1045642 is associated with the risk of breast, renal, blood, and other cancers (Mhaidat et al, 2011;Qian et al, 2012;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, among Caucasians, the C3435T polymorphism in exon 26 correlates with expression of P-gp in the intestine, and people who are homozygous for the T allele show more than 2-fold lower duodenal P-gp protein expression levels compared with C homozygotes. Since concentrations of P-gp in the intestine determine the extent of drug absorption, genotype-related differences in bioavailability are seen for several drugs (e.g., digoxin) (Chen et al, 2011;Li et al, 2011;Yan et al, 2011;Ponnala et al, 2012). Substantial differences in allele frequencies have been reported in different racial groups.…”
Section: Introductionmentioning
confidence: 99%